Is mean platelet volume a better biomarker in pre‐eclampsia?. Issue 6 (19th April 2017) - Vilchez, Gustavo; Lagos, Moraima; Kumar, Komal; Argoti, Pedro
Abstract: Aim: Platelet activation and destruction is a well recognized feature of pre‐eclampsia, but the current literature is contradictory regarding the role of mean platelet volume (MPV) in the diagnosis of this condition. We investigated whether MPV, compared with other routine laboratory markers such as platelet count, is a more significant biomarker of pre‐eclampsia, giving special attention to the intrapartum period. Methods: Biochemical and hematological markers along pregnancy including MPV were compared retrospectively between pre‐eclampsia and matched controls. Laboratory marker data were compared using independent t ‐test. A logistic regression model was used to compare the strength of the associations of MPV and other routine markers such as platelet count with pre‐eclampsia. Receiver operating characteristic curves were plotted. Results: There were a total of 150 cases of pre‐eclampsia and 297 controls. In the pre‐eclampsia group, there were 60 cases of mild pre‐eclampsia (40.0%); 84, severe (56.0%); and six of eclampsia (4.0%). MPV was significantly higher in the pre‐eclampsia than in the control group (11.3 ± 1.0 vs 10.1 ± 0.8 fL, P = 0.002). On multivariate analysis, MPV was the only statistically significant biomarker of pre‐eclampsia (OR, 4.5; 95%CI: 1.5–13.7), and severe pre‐eclampsia (OR, 6.2; 95%CI: 1.6–24.6); performing superiorly to platelet count. Conclusions: Mean platelet volume is a more significant biomarker of pre‐eclampsia. It is more significantly associated with this condition than other routinely measured laboratory markers such as platelet count. MPV is routinely obtained on complete blood cell count and its utilization in the assessment of pre‐eclampsia in a clinical setting should continue to be evaluated.